Dicalcium silicate microparticles modulate the differential expression of circRNAs and mRNAs in BMSCs and promote osteogenesis via circ_1983–miR-6931–Gas7 interaction. (28th May 2020) - Zhong, Wenchao; Li, Xingyang; Pathak, Janak L.; Chen, Liangjiao; Cao, Wei; Zhu, Mingjing; Luo, Qianting; Wu, Antong; Chen, Yunxin; Yi, Lingbo; Ma, Manyuan; Zhang, Qingbin
Abstract : Among C2 S-induced differentially expressed circRNAs, circ_1983 is involved in osteogenesis via circ_1983–miR-6931–Gas7 ceRNA interaction-mediated Runx2 upregulation. Abstract : Dicalcium silicate microparticle (C2 S)-based biomaterials have a potential for bone and dental tissue regenerative applications. The C2 S-mediated transcriptome level mechanism in mesenchymal stem cells (MSCs) during bone-defect healing has not been investigated yet. In this study, we elucidated the differential expression pattern of messenger RNAs (mRNAs) and circular RNAs (circRNAs) in C2 S-treated MSCs and their involvement in the osteogenesis process. C2 S robustly enhanced the osteogenic differentiation of MSCs and cranial bone defect healing. C2 S-treatment modulated the differential expression of mRNAs and circRNAs in MSCs. Differentially expressed circRNAs and mRNAs were involved in competing endogenous RNA (ceRNA-interaction networks). These ceRNA-interaction networks regulated the signaling pathways associated with osteogenesis, e.g., Wnt, PI3K-Akt, MAPK, and JAK/STAT signaling. C2 S-treatment upregulated the expression of circ_1983, Gas7, and Runx2 in BMSCs. RNase R and luciferase activity assay confirmed the stability and miR-6931 sponging property of circ_1983, respectively. Knockdown of circ_1983 enhanced miR-6931 expression but inhibited Gas7 and Runx2 expression and osteogenic differentiation in C2 S-treated MSCs. In conclusion, for the first time, we report the role of cicr_1983–miR-6931–Gas7 ceRNA-interaction in C2 S-induced osteogenic differentiation of MSCs and bone defect healing. This study opens a new research stream "the role of circRNAs-mediated ceRNA-interaction in biomaterials and stem cell-based bone tissue engineering".